Air‐stable inorganic solid‐state electrolytes for high energy density lithium batteries: Challenges, strategies, and prospects. Issue 1 (6th September 2021) - Chen, Xuanfeng; Guan, Zengqiang; Chu, Fulu; Xue, Zhichen; Wu, Feixiang; Yu, Yan
Abstract: Solid‐state batteries have been considered as promising next‐generation energy storage devices for potentially higher energy density and better safety compared with commercial lithium‐ion batteries that are based on organic liquid electrolytes. However, in terms of indispensable solid‐state electrolytes, there are remaining issues to be solved before entering the market. Most solid‐state electrolytes are air‐sensitive, which causes a complex and expensive cell assembly and impressible interface. Therefore, the solid‐state electrolytes are expected to be atmosphere‐stable, which will undoubtedly bring significant benefits to solid‐state battery manufacturing. This review covers air‐stability‐related issues of different types of inorganic solid‐state electrolytes and the corresponding strategies. First, we provide an overview of solid‐state electrolytes and solid‐state batteries, including their history and advantages/disadvantages. Then, different types of solid‐state electrolytes are selected as examples to illustrate the unfavorable interactions in air and the corresponding adverse effects. Next, according to recent advances, we summarize the effective strategies of constructing different types of air‐stable inorganic solid‐state electrolytes. Finally, perspectives on designing accessible air‐stable solid‐state electrolytes are provided, aiming to achieve the assembly of high‐performance solid‐state batteries in the atmosphere. Abstract : Air‐stable solid‐state electrolytes are very promising electrolyte candidates for next‐generation rechargeable lithium and lithium‐ion batteries. In this review article, the air‐instability of various solid electrolytes are discussed in detail, as well as the corresponding degradation mechanisms. In turn, the recent advances of developing effective strategies to overcome chemical sensitivity of different solid electrolytes in air are summarized, which provides guidelines to construct air‐stable solid‐state electrolytes. Radar plots of properties of sulfide SSEs, garnet SSEs, perovskite SSEs, anti‐perovskite SSEs, polymer SSEs, and NA/LISICON SSEs (in ascending order of air stability).